Evaluation of different precision hoeing methods and soil physical properties of re-compacted ridge tillage systems in corn - Oyebanji O. Alagbo; Marcus Saile; Michael Spaeth; Matthias Schumacher; Markus Sökefeld; Roland Gerhards (Weed Technology)
This study aimed to evaluate different precision hoeing methods on re-compacted ridges. It also aimed to evaluate the impact of ridge re-compaction on soil temperature and moisture retention. Five weeding trials were conducted in corn fields from 2022 to 2024 using two different ridge cultivators, Glühfosator and Damm Profi. The treatments included hoeing (HOE-2), hoeing combined with band herbicide spraying (HOE-1), hoeing combined with living mulch sown in the ridge valleys (HOE-3), and hoeing combined with postemergence harrow (HOE-4). Nontreated control and broadcast herbicide plots were included as controls. Soil moisture and temperature were recorded at 20-min intervals from May to September. Weed species composition, weed biomass, and corn silage yield were measured. Broadleaf weeds were the dominant weed species observed in all corn trials. In most trials, the hoeing treatments were not significantly different from that of applying a broadcast herbicide. Interrow areas treated with side-cut knives and ridge re-builders (HOE-1, HOE-2, and HOE-3) produced a significantly reduced weed biomass (4 to 55 g m−2) and exhibited high (80% to 96% weed control efficacy (WCE) across all trials. Intrarow-treated areas (i.e., tops of ridges) with a band herbicide (HOE-1), no-till sweeps (HOE-2, HOE-3), and postemergence harrow (HOE-4) resulted in 88% to 100%, 30% to 63%, and 17% WCE, respectively. Depending on corn cultivar and ridge cultivator, the HOE-1, HOE-4, and HOE-2 treatments resulted in corn silage yield that was similar to or greater than that of a broadcast herbicide. Yield was increased by 2000 to 9000 kg ha−1 after the HOE-1 treatment, by 2000 to 5000 kg ha−1 after the HOE-4 treatment, and by 3000 to 6000 kg ha−1, after the HOE-2 treatment. When rainfall was limited, re-compacted ridges demonstrated moisture conservation, which resulted in higher day-warming and lower night-cooling of ridge valleys (compared to ridge areas and flat-tilled beds), whereas when rain is heavy, ridges drained moisture and exhibited higher day-warming and lower night-cooling of ridge areas. These results suggest that precision hoeing on ridges could alternate broadcast herbicide use, while re-compacted ridges prove resilient to extreme rainfall events.